2011
DOI: 10.1682/jrrd.2010.19.0199
|View full text |Cite
|
Sign up to set email alerts
|

Effects of type and mode of propulsion on hand-cycling biomechanics in nondisabled subjects

Abstract: Abstract-This study investigated the range of motion (ROM) (in degrees) of the upper limb and trunk, forces (Newtons), twodimensional fraction effective force (FEF 2D ) (in percent), and torque (Newton meters) during hand cycling. Seven nondisabled participants performed a 1 min exercise test at 70 rpm on a hand cycle (HC) fixed to an ergometer in synchronous (SC) mode versus asynchronous (AC) mode and in arm-power (AP) versus arm-trunk-power (ATP) type of propulsion. Higher (p < 0.001) flexion/extension of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…As related to the current study of kinematics in the sagittal plane (flexion/ extension movements), these results must be interpreted cautiously as they might not apply to arm-cycling sprinting. In addition, in the current study, the configuration of the ergometer and the variables of intensity and speed were different from previous studies (50,55,57,58). As Botzheim et al (50) suggested, those differences affect muscle activation and could potentially change the kinematics of the movement task.…”
Section: Discussioncontrasting
confidence: 66%
“…As related to the current study of kinematics in the sagittal plane (flexion/ extension movements), these results must be interpreted cautiously as they might not apply to arm-cycling sprinting. In addition, in the current study, the configuration of the ergometer and the variables of intensity and speed were different from previous studies (50,55,57,58). As Botzheim et al (50) suggested, those differences affect muscle activation and could potentially change the kinematics of the movement task.…”
Section: Discussioncontrasting
confidence: 66%
“…In a more biomechanical approach with a handcycle-ergometer set-up, Faupin et al (2011) found more range of motion of the trunk, shoulder and elbow in the asynchronous mode. The torque produced in the synchronous mode was significantly lower during the pull phase and significantly higher during the push up than during asynchronous handcycling, indicating a different propulsion style between modes [15].…”
Section: Introductionmentioning
confidence: 88%
“…it is easier to steer when moving the arms symmetrically (van der Woude et al 2000). Related is also that trunk muscle activity is increased and more continuous during asymmetrical compared to symmetrical handcycling, resulting in higher rotation and lateral flexion of the trunk to propel and stabilize the participant and the steering Faupin et al 2011). This increase in muscle activity to stabilize steering direction appears to increase the energy cost during asymmetrical handcycling (Dallmeijer et al 2004; van der Woude et al 2008).…”
Section: Introductionmentioning
confidence: 99%